Assessing the Quality of Public Space for Sustainable Tourism in Sabang City - Fachrurrazi, Fachrurrazi; Nabilah (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2025)
Sabang City recognized as a national strategic tourism area and cruise port in western Indonesia, has significant potential to develop inclusive and sustainable tourism. However, the current condition of its public spaces remains suboptimal. This study aims to assess the quality of public spaces in Sabang based solely on field observations using ten sustainability-based indicators derived from a literature review: accessibility, safety and comfort, cleanliness and maintenance, visual appeal, diversity of functions and facilities, sociocultural value, visitor behavior patterns, economic integration, stakeholder collaboration, and environmental awareness Field observations were conducted across seven public space locations from December 2 to 14, 2024. The findings reveal that collaboration, diversity of functions, and economic integration scored the lowest, with averages below 1.5 on a 4-point scale, while visual and environmental quality emerged as the only indicator with a consistently high score above 3.5. Most other indicators, such as accessibility and safety, remained below 2.5, indicating critical gaps in inclusivity, functionality, and user comfort. These deficiencies are attributed to limited budget allocations and weak inter-agency coordination, as confirmed through supporting interviews with local government officials. The results underscore the need for improved planning, maintenance, and inter-sectoral collaboration to ensure that public spaces can serve as inclusive, multifunctional, and environmentally responsible infrastructure that supports long-term tourism development. This study provides a replicable indicator-based assessment framework and highlights specific areas for policy intervention to enhance the role of public spaces in Sabang’s sustainable tourism strategy.